Biofouling in membrane bioreactors: nexus between polyacrylonitrile surface charge and community composition. Issue 3 (16th March 2018) - Marbelia, Lisendra; Hernalsteens, Marie-Aline; Ilyas, Shazia; Öztürk, Basak; Szymczyk, Anthony; Springael, Dirk; Vankelecom, Ivo
Abstract: The influence of membrane surface charge on biofouling community composition during activated sludge filtration in a membrane bioreactor was investigated in this study using polyacrylonitrile-based membranes. Membranes with different surface properties were synthesized by phase inversion followed by a layer-by-layer modification. Various characterization results showed that the membranes differed only in their surface chemical composition and charge, ie two of them were negative, one neutral and one positive. Membrane fouling experiments were performed for 40 days and the biofouling communities were analyzed. PCR-DGGE fingerprinting indicated selective enrichment of bacterial populations from the sludge suspension within the biofilms at any time point. The biofilm community composition seemed to change with time. However, no difference was observed between the biofilm community of differently charged membranes at specific time points. It could be concluded that membrane charges do not play a decisive role in the long-term selection of the key bacterial foulants.